Pemanfaatan Teknologi dalam Pembelajaran - Alisia Zahroatul Baroroh; Diyah Andini Kusumastuti; Rahmat Kamal (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
The use of technology in learning has become an increasingly important phenomenon in the world of education, especially in today's digital era. Technology not only improves accessibility and flexibility in learning, but also enriches the learning experience by presenting more interactive and engaging materials. This research aims to analyze the application of technology in learning and explore the benefits, challenges, and opportunities that exist. Based on the results of research conducted in several educational institutions, it was found that the use of online learning platforms, educational applications, and multimedia-based media is able to increase student engagement, provide wider access to learning resources, and create a more personalized learning experience. However, challenges such as the digital divide, limited infrastructure, and low digital literacy among educators are still obstacles that need to be overcome. In conclusion, while technology offers a variety of advantages, its use must be done wisely taking into account the local context and efforts to improve digital access and skills for all parties involved.